Diffuse Large B Cell Lymphoma with Extensive Cutaneous Relapse. (20th September 2015) - Malkan, Umit Yavuz; Gunes, Gursel; Yayar, Okan; Demiroglu, Haluk
Abstract : Herein, we aimed to report a diffuse large B cell lymphoma (DLBCL) case that had extensive cutaneous relapse with no skin involvement previously. A 59-year-old man presented to hospital in April 2014 with fatigue, anorexia, fever, and anemia. Cervical lymph node biopsy revealed CD20+, BCL2+, MUM1+, BCL6+ high grade B lymphoproliferative neoplasm. After FISH investigation, he was diagnosed as DLBCL. He was given 7 cycles of R-CHOP and achieved remission. However, in November 2014, he had emerging skin lesions that cover nearly all of his body. A control PET-CT revealed diffuse cutaneous involvement. CD20+, BCL2+, MUM1+, BCL6+ high grade B cell lymphoma infiltration was detected with skin biopsy. He was diagnosed as relapse lymphoma, so 2 cycles of R-DHAP were given. There was no treatment response; therefore, R-ICE regimen was started. The patient had achieved second complete remission and his skin lesions were completely regressed. The involvement of skin with CD20+ cells after 7 cycles of rituximab therapy favors that there is a rituximab resistant disease which tends to involve the skin. To conclude, DLBCL may relapse extensively with cutaneous involvement and the best treatment option in these patients is salvage chemotherapy followed by autologous peripheral blood stem cell transplantation.